Multiwavelength Brillouin/Erbium-Ytterbium fiber laser - Abd Rahman, Faidz; Harun, Sulaiman Wadi; Emami, Siamak Dawazdah; Muhd-Yassin, S. Z.; Abd-Rahman, M. K.; Ahmad, Harith (IOP Publishing, 2007)
A multi-wavelength Brillouin/Erbium-Ytterbium doped fiber laser which operates in the 1535 nm region is proposed and demonstrated. The system employs both linear and nonlinear gain from a 4 meter Erbium-Ytterbium doped fiber and an 8 km single mode fiber respectively to generate an optical comb with a spacing of approximately 0.084 mn. A stable output laser comb of more than 22 lines was obtained with a Brillouin pump of 2 dBm and a 1058 nm pump of 175 mW. A maximum peak power of -4.2 dBm was obtained at a wavelength of 1535.16 nm at these pump power settings while the spectral linewidth of the laser is approximately 8 Hz.